Question
upstudy study bank question image url

Use implicit differentiation to find \( \frac{d y}{d x} \) \( 5 y^{2}=\frac{3 x-2}{3 x+2} \)

Ask by Davies Boone. in the United States
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\[ \frac{dy}{dx} = \frac{6}{5y(3x + 2)^2} \]

Solution

We start with the equation   5y² = (3x – 2)/(3x + 2). Step 1. Differentiate both sides with respect to x. Remember that y is a function of x, so when differentiating y², use the chain rule. The derivative of the left-hand side (LHS) is:   d/dx(5y²) = 5·2y·(dy/dx) = 10y·(dy/dx). Step 2. Differentiate the right-hand side (RHS). We have a quotient, so use the quotient rule. For a function f(x)/g(x),   d/dx[f(x)/g(x)] = (f′(x)·g(x) – f(x)·g′(x))/(g(x))². Let f(x) = 3x – 2 and g(x) = 3x + 2. Then:   f′(x) = 3  and  g′(x) = 3. Thus,   d/dx[(3x – 2)/(3x + 2)] = [3·(3x + 2) – (3x – 2)·3] / (3x + 2)². Simplify the numerator:   3(3x + 2) – 3(3x – 2) = (9x + 6) – (9x – 6) = 12. So the derivative of the RHS is:   12 / (3x + 2)². Step 3. Set the derivatives equal to each other:   10y·(dy/dx) = 12/(3x + 2)². Step 4. Solve for dy/dx by isolating it:   dy/dx = 12 / [10y·(3x + 2)²]. Simplify the fraction (divide numerator and denominator by 2):   dy/dx = 6 / [5y·(3x + 2)²]. Thus, the derivative of y with respect to x is:   dy/dx = 6/(5y(3x + 2)²).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To find \( \frac{d y}{d x} \) using implicit differentiation, we start with the equation \( 5 y^{2} = \frac{3 x - 2}{3 x + 2} \). First, differentiate both sides with respect to \( x \). For the left side, we have: \[ \frac{d}{dx}(5y^{2}) = 10y \frac{dy}{dx} \] For the right side, we use the quotient rule: \[ \frac{d}{dx}\left(\frac{3x - 2}{3x + 2}\right) = \frac{(3)(3x + 2) - (3)(3x - 2)}{(3x + 2)^{2}} = \frac{9x + 6 - (9x - 6)}{(3x + 2)^{2}} = \frac{12}{(3x + 2)^{2}} \] Now, we set the derivatives equal to each other: \[ 10y \frac{dy}{dx} = \frac{12}{(3x + 2)^{2}} \] To solve for \( \frac{dy}{dx} \), we rearrange the equation: \[ \frac{dy}{dx} = \frac{12}{10y(3x + 2)^{2}} = \frac{6}{5y(3x + 2)^{2}} \] Thus, the derivative \( \frac{dy}{dx} \) is given by: \[ \frac{dy}{dx} = \frac{6}{5y(3x + 2)^{2}} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy